Umpatan Dalam Bahasa Pergaulan Siswa SMA di Denpasar - Ni Wayan Meidariani; I Wayan Wahyu Cipta Widiastika; Wayan Nurita (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
Swearing involves using harsh words and is employed in both serious and casual contexts. Most swearing is studied based on its use in speech as a sociolinguistic study. Based on this, it is very important to discuss swearing based on the relationship of its constituent elements with a semantic approach so that the meaning of swearing is known based on the relationship of the referred referents. This study aims to elucidate the meaning of swearing in relation to the constituent elements of cognitive semantics. Thus, the meaning and function of swearing in the slang of high school students are known. This type of research is qualitative, focusing on oral communication in slang within the high school student community. Data were obtained from observations of communication among high school students in Denpasar who were born between 2008 and 2010. Data collection used observation and interview methods. The study's results found that high school students in Denpasar use animal words, such as